Comparison of Antibiotic Susceptibility Patterns of Bacterial Isolates Based on Time From Hospitalization and Culture Source: Implications for Hospital Antibiograms. (13th November 2015) - Dickstein, Yaakov; Geffen, Yuval; Leibovici, Leonard; Paul, Mical
Abstract : We assessed the effects of time from hospitalization and culture source on bacterial susceptibility profiles. Increasing resistance correlated with increasing time from hospitalization for all bacterial groups, with 7 days in hospital representing the best time point for dichotomizing susceptibility rates rather than 48 hours. Antibiograms based on isolates from any source best represented susceptibility profiles. Infect. Control Hosp. Epidemiol. 2016;37(2):212–214